(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Monosodium glutamate (MSG) is a widely-consumed taste enhancer which has been implicated in the aetiology of renal and hepatic dysfunction in adults and their offspring. There is increasing evidence on the therapeutic properties of Coconut Water (CW) in kidney and liver disorders. This study investigated the effects of CW on renal and hepatic functions in offspring of MSG-fed dams. Twelve female Wistar rats (120 – 140 g) were grouped into four as follows; Control (10 ml/Kg distilled water), MSG (0.08 mg/Kg), CW (10 ml/Kg) and MSG+CW. Treatments were given orally daily commencing two weeks prior to mating, throughout mating and gestation until parturition. All dams received standard rodent diet and drinking water ad libitum throughout the study. After weaning on Post-Natal Day (PND) 28, serum was obtained from offspring for assay of liver and renal function. Histological analysis of the livers and kidneys were performed on both dams and offspring. There was no significant difference in liver enzymes, urea, creatinine and albumin levels amongst the offspring on PND 28. However, liver and kidney sections from MSG dams and their offspring showed early degenerative changes which were not evident in renal and hepatic tissues from CW and MSG+CW dams and offspring. These observations suggest that coconut water protects against monosodium glutamate-induced renal and hepatic dysfunction in dams and offspring.